2018
DOI: 10.3390/risks6030094
|View full text |Cite
|
Sign up to set email alerts
|

Country Risk Ratings and Stock Market Returns in Brazil, Russia, India, and China (BRICS) Countries: A Nonlinear Dynamic Approach

Abstract: This study examines the linkages between Brazil, Russia, India, and China (BRICS) stock market returns, country risk ratings, and international factors via Non-linear Auto Regressive Distributed Lags models (NARDL) that allow for testing the asymmetric effects of changes in country risk ratings on stock market returns. We show that BRICS countries exhibit quite a degree of heterogeneity in the interaction of their stock market returns with country-specific political, financial, and economic risk ratings. Posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…They concluded that the CDS spread is the most important indicator for the countries that affect global risk. Similar to this study, Nasr et al [13], Korotaev et al [14], Acosta et al [15], and Shostya and Banai [16] also tried to evaluate the global risk of different countries. Additionally, Avdjiev et al [17] analyzed that the dollar exchange rate is a significant factor of global risk.…”
Section: A Literature Review Of Global Risks and Financial Crisesmentioning
confidence: 53%
“…They concluded that the CDS spread is the most important indicator for the countries that affect global risk. Similar to this study, Nasr et al [13], Korotaev et al [14], Acosta et al [15], and Shostya and Banai [16] also tried to evaluate the global risk of different countries. Additionally, Avdjiev et al [17] analyzed that the dollar exchange rate is a significant factor of global risk.…”
Section: A Literature Review Of Global Risks and Financial Crisesmentioning
confidence: 53%
“…Nasr et al ( 2018) [22] provide a qualitative overview regarding the linkages between BRICS countries and highlight the heterogeneity in stock market returns based on several underlying criteria. Their main conclusion is that BRICS countries react differently regarding the rating changes, depending upon their connections with the global market variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Balcilar et al (2017) showed that Brazil, Russia, India, China and South Africa (BRICS) stock returns demonstrated heterogeneous exposures to geopolitical risks, with the highest effect being in Russia. In this context, Nasr et al (2018) showed through non-linear ARDL that there exists a high heterogeneity in BRICS returns’ interaction with country-based risk components. They concluded that bad news or negative changes in the ratings have a greater effect on stock returns and that there is a similarity in the interaction of the BRICS stock market with rating changes and its interaction with global indicators.…”
Section: Review Of Literaturementioning
confidence: 99%